A path to community development: The community reinvestment act, lending discrimination, and the role of community development banks - Dimitri B. Papadimitriou; Ronnie J. Phillips; L. Randall Wray (Levy Economics Institute of Bard College, 1993)
The establishment of a system of federally regulated, for-profit community development banks (CDBs) would help to fill the financial gap in areas inadequately served by traditional banks, requirements of the Community Reinvestment Act (CRA) notwithstanding. These organizations would be charged with delivering credit, payment, and savings opportunities and providing basic financing to households and small businesses in underserved areas. Such a system would not substitute for the CRA, but rather act as a supplement to current regulation. Proposed exemptions from CRA compliance for depository institutions that invest in the equity of a CDB would weaken the existing law by diluting the investment of the depository institution in its own particular community. Such proposals (under which investment has been defined to be as little as one-quarter of one percent of total assets) are not consistent with the spirit of the CRA and would negate the beneficial dialogue that takes place between the institution and the community in which it operates.
Keywords: 330